2007
DOI: 10.1186/1744-859x-6-2
|View full text |Cite
|
Sign up to set email alerts
|

An observational study in psychiatric acute patients admitted to General Hospital Psychiatric Wards in Italy

Abstract: Objectivesthis Italian observational study was aimed at collecting data of psychiatric patients with acute episodes entering General Hospital Psychiatric Wards (GHPWs). Information was focused on diagnosis (DSM-IV), reasons of hospitalisation, prescribed treatment, outcome of aggressive episodes, evolution of the acute episode.Methodsassessments were performed at admission and discharge. Used psychometric scales were the Brief Psychiatric Rating Scale (BPRS), the Modified Overt Aggression Scale (MOAS) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…As a positive treatment response is usually defined in the literature as greater than 20% reduction in BPRS (Lachar et al, 1999), our findings showed that a short LOS in our ward was highly effective. Our results are consistent with previous systematic reviews (Alwan et al, 2008;Johnstone and Zolese, 2009) and the two Italian surveys (Ballerini et al, 2007a(Ballerini et al, , 2007bBarbato et al, 2010;Preti et al, 2009), suggesting that a short hospitalization is sufficient for the majority of patients (Frieri et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…As a positive treatment response is usually defined in the literature as greater than 20% reduction in BPRS (Lachar et al, 1999), our findings showed that a short LOS in our ward was highly effective. Our results are consistent with previous systematic reviews (Alwan et al, 2008;Johnstone and Zolese, 2009) and the two Italian surveys (Ballerini et al, 2007a(Ballerini et al, , 2007bBarbato et al, 2010;Preti et al, 2009), suggesting that a short hospitalization is sufficient for the majority of patients (Frieri et al, 2013).…”
Section: Discussionsupporting
confidence: 95%
“…Given the necessity for immediate treatment in patients suffering from acute agitation either with schizophrenia or bipolar mania, there is a warranted clinical need for very rapid pharmacological intervention. The availability of rapid-acting IM formulations of psychotropic medications and in particular those of the SGA, with rapid efficacy and a more favorable EPS profile represents a valuable alternative in the treatment acute episodes of agitation in patients with schizophrenia or bipolar acute mania [24,8,21].…”
Section: Discussionmentioning
confidence: 99%
“…This structure remains stable across the longitudinal course of schizophrenia (Kopelowicz et al, 2008) and cross-culturally (Ruggeri et al, 2005). The 24-item BPRS is also a sensitive measure of symptom reduction occurring after rehabilitation intervention (Ballerini et al, 2007; Gigantesco et al, 2006; Inch et al, 1997; Pioli et al, 2006). Moreover, less clinically experienced professionals could administer the BPRS 4.0 with high levels of inter-rater reliability (Roncone et al, 1999; Ventura et al, 1993a).…”
Section: Introductionmentioning
confidence: 99%